Planejamento por modelagem molecular e síntese de inibidores potenciais de serino proteases - Ana Carolina de Oliveira (2009)
Serine proteases are a class of enzymes of great therapeutic importance. Their role in critical biological processes like digestion, blood coagulation, fibrinolysis and immune response make them promising targets for the development of new drugs. Aiming at the synthesis of potential serine protease inhibitors a set of ten moleculeswas subjected to a molecular modeling study (docking) using the AutoDock 3.0.5 program. The goal of this study was to determine the binding affinity and modes of binding of the potential inhibitors to â- trypsin. â-trypsin was chosen for the present work because it is considered a model for the study of serine proteases. Among the compounds subjected to docking four were selected for synthesis.Compounds 1,3-bis(1-naftiloxi)-2-[(4-amidinobenzoil)amino]propane (7) and 1,3- bis(2-naftiloxi)-2-[(4-amidinobenzoil)amino]propane (8) were chosen because of their higher affinity as expressed by their higher pKi values as compared to the other compounds. N-(4-nitrofenil)-4-amidinobenzamide (1) and N-benzil-4- amidinobenzamide (2) were those with the lower pKi values and they were selected for synthesis for method validation reasons.The compounds 2, 7 and 8 were obtained successfully and they will be evaluated in enzymatic assays to be carried out in the laboratory of collaborators of the present project (professor Amintas Fabiano de Souza and professor Marcelo Matos Santoro). The attempts to synthesize 1 resulted in starting material recovery or in the isolation of p-nitroaniline, a hydrolysis product.